The space produced and consumed by highways: the case of the enlargement of the Tamoios Highway – SP (Revista Espinhaço, 2014)
This article discusses the socially produced and consumed space as it is initially transformed into the realm of ideas and in this case, from the perspective of the capitalist ideal and that is consolidated through political alliances that will provide thenecessary conditions for this idea to be materialized in the geographical space. This form of physical structure is called structuring axis in this paper and that it will provide that significant transformations occur. The presented example is the Brazilian highwaysthat polarized economic growth in several regions of the country, a model of growth strongly based on the ideology of mobility centered in the car. To discuss this issue, this paper focuses on the upgrading and enlargement process of the Tamoios Highwayand its potential impacts over the cities located on its axis and the lack of integration of these cities in the context of regional development policies.
Keywords: space; consumption; highways; mobility